(untitled) (Research, Society and Development, 2020)
To describe the distribution of asthma self-reporting and identify the associated factors in Brazilian schoolchildren, according to region and gender. This is a cross-sectional study using data from PeNSE 2015 Sample 1 (n = 95387). For the descriptive analysis, absolute and relative frequency measurements were used. To verify the factors associated with asthma in Brazilian adolescents, binary logistic regression was used, assuming the following hierarchical model: Sociodemographic Block: Sex, age, race; Environmental Block: Region, type of municipality; Behavioural Block: Tobacco consumption, level of physical activity, with the variable "did you ever have asthma in your life" being used as the endpoint, analysing the answer to the question "did you ever have asthma in your life? There was a higher prevalence of self-reported asthma episodes in females (51.7%), with a higher probability of self-reported asthma (OR=1.07; 95%CI 1.03-1.11) than in males. The non-resident population was 28% less likely to self-report asthma (OR=0.78; 95%CI = 0.75-0.80), and the non-asthmatic adolescent was 12% less likely to be active (OR=0.88; 95%CI = 0.85-0.91). The prevalence of self-reported episodes of asthma is lower for residents of the Midwest Region. However, it is higher among females, in adolescents living in the Brazilian state capitals, and asthma sufferers tend to be more active than their peers.